KESENJANGAN PERALATAN DAN TEKNOLOGI PADA SEKOLAH ATAU PUSAT PELATIHAN VOKASIONAL - Pramudya Pradana Fauzani (CV. ADIBA AISHA AMIRA, 2024)
One of the educational systems that exists in Indonesia is the vocational education system. Vocational education purpose is to produce ready-to-work graduates who have the relevant skills for current job employment. The ability of hard skills and soft skills plays a central, vital, and urgent role for vocational education. Industrial world hope that vocational education graduate have competencies in the form of adequate, superior, capable, and qualified hard skills and soft skills.In vocational learning, practical facilities are very important in supporting the learning process which according to the concept of vocational learning is to prioritize practice. The educational process of course, requires adequate facilities or infrastructure. If the school has facilitated by providing infrastructure to support learning, then both teachers and students will be able to utilize and optimize the learning process and training activities at school. Therefore, this research was conducted to determine the influence of availablity facilities and infrastructure in the practical learning process.